Relevansi Alat Bukti Dalam Sistem Peradilan Pidana Indonesia: Analisis Normatif Dan Praktis - Reftahu Janna; Ria Anggraeni Utami (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Evidence is a key element in criminal cases in Indonesia. The legal framework for proof as regulated by the Criminal Procedure Code (KUHAP) adheres to a negative statutory system of proof, which combines a minimum amount of evidence and the judge's conviction. However, the development of information technology and the emergence of modern forms of crime have created a need to evaluate the relevance of these types of evidence that are regulated in a limited manner. This article uses a normative juridical approach and is supported by practical analysis through judicial theory and practice. The results indicate that the Indonesian evidentiary system requires substantial reform, particularly in the regulation of electronic evidence and scientific examination standards.